Актуальні напрями архітектурної освіти на кафедрі ДАС НУ «Львівська політехніка» в умовах війни та після перемоги - Проскуряков, Віктор; Богданова, Юлія; Копиляк, Ігор; Proskuryakov, Viktor; Bohdanova, Yuliia; Kopylyak, Ihor (Видавництво Львівської політехніки, 2023)
В статті висвітлено широку палітру робіт, які були виконані студентами кафедри дизайну архітектурного середовища в рамках навчального та дипломного проєктування для потреб відбудови України після російського вторгнення. Також було відзначено актуальність використання завдань, пов’язаних з відновленням громадських житлових та ландшафтних об’єктів, у навчальному процесі підготовки майбутніх кадрів, на початок професійної діяльності яких припаде основна фаза реновації міст та поселень.

As of the beginning of 2023, the destruction of many facilities and the environment as a result of the war unleashed by the Russian aggressor in Ukraine has made it urgent to rebuild everything lost not only in peacetime, after the victory, but also now, when active hostilities are underway. The challenge of today is to quickly and effectively restore everything that has been destroyed and create new opportunities for the near and far future. A lot has been lost: more than 149.3 thousand residential buildings; 3 thousand secondary, pre-school and higher education institutions; almost 1500 cultural, sports and tourism facilities; about 100 religious sites; 330 hospitals; 595 administrative buildings and much more. Our society will never be able to fully restore the architecture and environment of Ukraine, relying only on measures initiated by the authorities from above. Financial and organizational support alone is not enough to revive everything destroyed by the war in Ukrainian cities and towns. And the architecture of Ukraine can be restored not so much by foreign architectural stars as by our own, Ukrainian creators of architecture. Architectural education is also of great importance in this process. After all, senior students will be the direct implementers of the ideas that are being generated today. Therefore, their training, both theoretical and practical, should be developed now in the process of studying at higher education institutions. The article highlights a wide range of works that were performed by students of the Department of Architectural Environment Design as part of their training and diploma design for the needs of rebuilding Ukraine after the Russian invasion. The article also emphasizes the relevance of using tasks related to the restoration of public housing and landscape objects in the educational process of training future personnel, whose professional activity will begin at the beginning of the main phase of the renovation of cities and settlements. This practice will allow students to better adapt and become competitive in the current labor market.
Current trends in architectural education at the department of dae of Lviv Polytechnic National University during the war and after the victory
Keywords: відбудова; міста; поселення; житлові будинки; заклади освіти і культури; торгові центри; ринки; парки; об’єкти монументального дизайну; reconstruction; cities; habitation; residential buildings; educational and cultural institutions; shopping centers; markets; parks; objects of monumental design; 721